Differences Month of Stock Chemotherapy Based on Consumption and Morbidity Methods at Mrccc Hospital - Feri Dian Sanubari; Agusdini Banun Saptaningsih; Rokiah Kusumapradja; Arrozi Arrozi (Syntax Corporation Indonesia, 2023)
The value of chemotherapy medicines' month of stock in MRCCC Siloam Hospitals Semanggi is high and is not comply to Head Office's standard of 0.66 months. Thus, an evaluation is needed to determine the differences between calculating Month of stock using consumption method and morbidity method. This is a retrospective, Empiric study using descriptive- comparative method with the purpose of explaining the most effective planning method to supply chemotherapy medicines. The study compares Month of stock of chemotherapy medicines using consumption and morbidity method. The result shows average value of Month of stock using morbidity method is 1.853 months and 2.125 months using consumption method. The morbidity method have lower avergae Month of stock compares to consuption method. Planning with a combination of the two methods obtained a Month of stock value of 1.41 months. Profitable than normal delivery. Efficiency is needed so that the hospital can develop better services in the future.